Correlation Analysis: AI Usage Frequency in Academic Writing Course and Plagiarism Awareness - Habiba, Habiba; Jaya, Hariswan Putera (Journal of English Language and Education, 2025)
In the digital era, plagiarism awareness has become increasingly important, especially with the rapid rise of artificial intelligence (AI) tools in academic writing. Applications such as ChatGPT, Grammarly, and Quillbot assist students in generating, editing, and refining texts, but they also blur the boundaries between legitimate support and potential misconduct. Previous studies have examined students’ perceptions of AI in relation to academic integrity and writing quality, yet few have directly investigated whether the frequency of AI use is associated with students’ plagiarism awareness. Addressing this gap, the present study examined the correlation between AI usage frequency and plagiarism awareness in an academic writing course. A total of 79 English Education students at Sriwijaya University participated in this quantitative study, with data analyzed using Pearson Correlation. The results revealed a positive but insignificant correlation between the two variables (r = 0.035, p = 0.761). These findings suggest that frequent use of AI tools does not automatically strengthen plagiarism awareness, highlighting the need for institutional regulations and explicit training in academic ethics to guide students toward responsible and ethical AI integration in their writing practices.